2015
DOI: 10.1080/15459624.2014.987384
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposures to Emissions from Combustion of Diesel and Alternative Fuels in Underground Mining—A Simulated Pilot Study

Abstract: Diesel fuel is commonly used for underground mining equipment, yet diesel engine exhaust is a known human carcinogen. Alternative fuels, including biodiesel, and a natural gas/diesel blend, offer the potential to reduce engine emissions and associated health effects. For this pilot study, exposure monitoring was performed in an underground mine during operation of a load-haul-dump vehicle. Use of low-sulfur diesel, 75% biodiesel/25% diesel blend (B75), and natural gas/diesel blend (GD) fuels were compared. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…The fuels, equipment, and study site description have previously been reported. 16 Briefly, ultra-low sulfur #2 diesel (Arizona Petroleum, Tucson, AZ) was used for diesel exposure testing, and B75 was prepared by mixing the aforementioned diesel fuel at 25% by volume with a soy methyl ester biodiesel fuel (ASTM D6751-compliant; Arizona Petroleum, Tucson, AZ). Exposure to vehicle emissions was evaluated during mucking activities in the San Xavier Mining Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The fuels, equipment, and study site description have previously been reported. 16 Briefly, ultra-low sulfur #2 diesel (Arizona Petroleum, Tucson, AZ) was used for diesel exposure testing, and B75 was prepared by mixing the aforementioned diesel fuel at 25% by volume with a soy methyl ester biodiesel fuel (ASTM D6751-compliant; Arizona Petroleum, Tucson, AZ). Exposure to vehicle emissions was evaluated during mucking activities in the San Xavier Mining Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…f 44 and f 43 values were located in the same area as the measurement data with EN590, however, f 44 was smaller and f 43 was larger during the NEXBTL period than on average in June ( Figure S3b). In a previous study of Lutz et al (2015), they have investigated the effect of biodiesel use on PM, OC, and EC concentrations in an underground mine. In that study, they found that 75% biodiesel/25% diesel blend was associated with reductions in respirable size PM and EC whereas respirable size OC did not change.…”
Section: Sources Of Sub-micrometer Particlesmentioning
confidence: 99%
“…There have, however, been three attempts (Table 3) at assessing the health effects of biodiesel exhaust exposure via epidemiology. [70][71][72] The first of these has significant drawbacks and is not published in a peer-reviewed journal. 70 In this study, 763 male road workers had their exposure to rapeseed biodiesel estimated from their job title.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…Similarly, Lutz et al (2015) performed personal exposure monitoring in an underground mine where equipment was fuelled with mineral diesel or a 75% biodiesel/25% diesel blend (B75). 71 Biodiesel emissions contained less PM mass under 1-μm particle size but more overall PM (in contrast with most other studies stating that overall PM is reduced with biodiesel) and more naphthalene. Biodiesel emissions also contained more total organic carbon and nitric oxide.…”
Section: Epidemiological Studiesmentioning
confidence: 99%